PENGGUNAAN LKPD DALAM PEMBELAJARAN IPS SD KELAS IV MATERI JENIS – JENIS PEKERJAAN DI SD NEGERI 200120 PADANGSIDIMPUAN - Kusuma Ningtyas, Rani; Sucahyo, Eko; Hutabarat , Febriana Sunita (Jurnal ADAM : Jurnal Pengabdian Masyarakat, 2025)
Student worksheets (LKPD) are a means to help and facilitate teaching and learning activities so that effective interactions will be formed between students and educators, so that they can increase student activity in improving learning achievement. said student worksheets (LKPD) are a learning resource that can be developed by educators as facilitators in learning activities. The prepared LKPD can be designed and developed according to the conditions and situations of the learning activities that will be faced. The method for implementing this community service that will later be implemented is a series of activity processes that have been structured and arranged systematically. The following is an overview of the activity process: (1) Problem Identification Stage; (2) Determining Problem Solving Strategies; (3) Problem Solving; (4) Carrying out Community Service; (5) Activity Evaluation. Student worksheets (LKPD) are a means to help and facilitate teaching and learning activities so that effective interactions will be formed between students and educators, so that they can increase student activity in improving learning achievement. Specific findings that explain the problem formulation, namely, how to apply LKPD teaching materials at SD Negeri 200120 Padangsidimpuan and how successful the use of LKPD is in the learning process, especially in social studies learning. Types of work. We found several things, namely: (1) Increasing student activity; (2) Can save learning time; (3) Can make students learn independently.